2015
DOI: 10.1371/journal.pone.0126610
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Anomalies in Children Exposed to Antithyroid Drugs In-Utero: A Meta-Analysis of Cohort Studies

Abstract: BackgroundHyperthyroidism affects about 0.2%-2.7% of all pregnancies, and is commonly managed with antithyroid drugs (ATDs). However, previous studies about the effects of ATDs on congenital anomalies are controversial. Therefore, the present meta-analysis was performed to explore the risk of congenital anomalies in children exposed to ATDs in-utero.MethodsEmbase, Pubmed, Web of Knowledge, and BIOSIS Citation Index were searched to find out studies about congenital anomalies in children exposed to ATDs in-uter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
2
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 41 publications
3
24
2
5
Order By: Relevance
“…The conclusions of the present review are in line with the results of a new meta-analysis published by Chinese analysts (18).…”
Section: Discussionsupporting
confidence: 87%
“…The conclusions of the present review are in line with the results of a new meta-analysis published by Chinese analysts (18).…”
Section: Discussionsupporting
confidence: 87%
“…The main disadvantage of RI is the conception delayed at least for 6 months; as to ATDs, they resolve the symptoms, but, when discontinued, the reappearance of the disease is certain. Moreover, due to the ATDs capability to cross the placenta, as well as to modulate foetal thyroid function, the pursuance of this therapy during pregnancy is to be avoided . In both male and female young patients, the RI therapy exposes them to radiation; the administered 15 mCi dose of 131 I to young men showed a reduced sperm motility, which can, therefore, determine infertility in subjects at risk .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, most studies have focused on the identification of risk factors of NSCL/P. Many epidemiological studies have confirmed that maternal age [10–12], maternal educational level [2, 13], family income [13, 14], abnormal reproductive histories [15], family history [14–16], history of infection during pregnancy [17], medication use during pregnancy [18, 19], ambient environment pollution [20], parental occupational hazards exposure [21–23], maternal nutrient intake [23–26], and maternal lifestyle factors (alcohol drinking, smoking) [27–29] are associated with NSCL/P. However, an individual risk prediction tool for NSCL/P has not been reported.…”
Section: Introductionmentioning
confidence: 99%